Infestation of the non‐photosynthetic plant Mitrastemon yamamotoi (Ericales: Mitrastemonaceae) by Assara balanophorae (Lepidoptera: Pyralidae). Issue 3 (4th July 2019) - Suetsugu, Kenji; Yoshiyasu, Yutaka
Abstract: Although the majority of Assara (Lepidoptera: Pyralidae) larvae feed on pinaceous cones, Assara balanophorae Sasaki & Tanaka is known to infest the infructescence of the holoparasitic plant Balanophora tobiracola Makino (Santalales: Balanophoraceae). Here, we report additional feeding ecology of A. balanophorae . We found that A. balanophorae larvae bored into the infructescence of the holoparasitic plant Mitrastemon yamamotoi Makino (Ericales: Mitrastemonaceae), pushing frass to the outside from small holes, and occasionally exited from the holes and consumed the scale leaves. Although Mitrastemon is distantly related to Balanophora at the order level, both plants could present a similar resource for A. balanophorae, due to their convergent holoparasitic characteristics. Given that A. balanophorae is considered as the brood‐site pollinator of Balanophora, rather than only parasitizing it, the morphological and ecological similarities between M. yamamotoi and Balanophora might suggest that the relationship between M. yamamotoi and A. balanophorae is also brood‐site pollination mutualism. Abstract : We report the infestation of non‐photosynthetic plant Mitrastemon yamamotoi by Assara balanophorae. Assara balanophorae is considered as the specialist on distantly related non‐photosynthetic plant Balanophora . The relationship between M. yamamotoi and A. balanophorae might be a rare example in which moths act as the pollinating parasites breeding on decaying floral tissues.